Eletroforese das proteínas séricas e urinárias de cães com erliquiose subclínica - Coelho, Stefanie Bertti [UNESP] (2015)
Ehrlichiosis is a hemoparasitosis that affects around 20 to 30% of dogs treated at veterinary clinics in Brazil, which may lead the animal to death. It predominate in the warmer regions of planet because of its intermediate host, an arthropod, that lives in high temperature regions. Due to the severity of the disease to animals and its zoonotic potencial, studies involving the possibles renal disorders are essential for the diagnosis and patient's prognosis. In this trial aimed to evaluate serum and urinary proteins of dogs with ehrliquiosis in the subclinical stage, by electrophoresis in poliacrilamida gel containing sodium dodecyl sulfate (SDS-PAGE). The animals were divided into control group (CG), 18 health dogs and sick group (SG), the last one with 17 dogs with diagnosis of erlichiosis subclinical, and the diagnosis of infection was conformed or excluded by association of clinical exams, serological tests and PCR. The results showed that dogs on the subclinical stage of ehrlichiosis had laboratory changes as thrombocytopenia, hyperglobulinemia associated with compensatory hypoalbuminemia and increased total protein, and anemia. From the serum electrophoresis, it was concluded that the infected dogs in subclinical phase had increased concentration of transferrin, the heavy chain of IgG, haptoglobin, alpha 1-acid glycoprotein and protein molecular weight 23 kDa. The analysis of urinary electrophoretic trace of the experimental animals, the result associated with the UPC, which shows borderline proteinuria in diseased dogs, showed that there renal lesions, both as tubular glomerular level, in dogs with erliquiosis in the subclinical stage, however, more studies are needed to clarify and better detail these injuries